(untitled) (LEARNing Landscapes, 2013)
Previously, video production was a skill set practiced by trained individuals, but new technologies have opened the doors so that anyone can be a filmmaker. This paper explores the history and conceptual foundations of participatory video (PV), and offers a reflective perspective on its applicability as a teaching and learning tool. A review of a PV training in Uganda is featured to highlight the methodology used in practice and the challenges faced. The authors propose that an approach to PV which combines the best existing practices with a closer alignment to its foundational principles is worthy of further research.